THE IMPACT OF GAME-BASED LANGUAGE LEARNING APPS ON STUDENT ENGAGEMENT AND PROFICIENCY - Putera, Zulmy Faqihuddin (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
Increasing student engagement and proficiency in the learning process is an important focus in education. One of the efforts made to achieve this goal is by utilizing game-based learning applications. This study aims to analyze the impact of using game-based learning media on student engagement and proficiency. The research method used is an experiment using independent sample t-test to analyze the data obtained from two groups of students, namely the experimental group that uses game-based applications and the control group that does not use these applications. The results showed that there was a significant difference in student engagement and proficiency between the two groups. Students who used the game-based application showed higher levels of engagement and proficiency compared to students who did not use the application. The implications of this study suggest that the use of game-based learning apps can be an effective strategy in improving student engagement and proficiency.